Legal Issues Related to Receiving Benefits from Social Security: Case Study of Section 77 Quarter - Sasiphattanakul, Sarinatcha (Mae Fah Luang University Law Journal, 2022)
The objective of this research was to study the comparative problems and solutions to the problem of payment of benefits to the beneficiary of social security, a case study of Section 77 Quarter when the insured dies. It was found that the problems of payment of benefits in case of death and old age when the insured dies According to the Social Security 1990 amended (No. 4), 2015, the person who is entitled to benefit from such cases: it does not meet the true intent or purpose of Social Security and also not up to date. When comparing the eligibility of the beneficiary in such cases from Thailand and foreign countries, it is found that foreign countries designate those who are entitled to receive benefits as heirs, not along with the law of the Social Security Act stipulated. Moreover, it does not comply with the Civil and Commercial Code in regard to the heirs and inheritance as well causing the heirs of the insured to go to court to show evidence for the confirmation. This action is considered as the aggravation of a victim rather than the help or alleviation despite the fact that some of that money is the insured’s money deducted while he or she is still alive. When the insured dies, it is difficult for the family to spend the money, or if there appears to be no heir who knows about the money, it will fall into the social security fund by default. Therefore, Section 77 Quarter of the Social Security Law should be amended to allow an adopted child to have the same rights as a child under the law of the insured. On account of the exception, it is unfair to an adopted child of the insured, which is inconsistent with the Civil and Commercial Law, Section 1627 which stipulates that an adopted child shall have the right of inheritance of the adopter as a descendant.